2016
DOI: 10.1094/cchem-09-15-0185-r
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a New Viscometer Performance in Predicting the Technological Quality of Soft Wheat Flour

Abstract: Cereal Chem. 93(4):364-368Gluten aggregation properties were investigated by means of the GlutoPeak device, a viscometer recently proposed as a rapid and sensitive test for measurement of wheat flour technological performance. In this study, 62 soft wheat flour samples of different quality and end use were utilized to evaluate if the GlutoPeak parameters could adequately predict chemical and rheological characteristics of soft wheat flour dough, that is, protein content measured by the Kjeldahl method, dough s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 11 publications
2
15
0
Order By: Relevance
“…If sufficient sample is available, the GlutoPeak test is recommended as a screening tool for gluten strength in durum wheat breeding programs. Similar support for the GlutoPeak as a fast and reliable tool for predicting bread wheat dough performance and soft wheat technological properties have been reported by others (Amoriello, Turfani, Galli, Mellara, & Carcea, 2016;Marti, Ulrici, Foca, Quaglia, & Pagani, 2015).…”
Section: Comparison Of Glutopeak Test With Other Dough Testssupporting
confidence: 84%
See 1 more Smart Citation
“…If sufficient sample is available, the GlutoPeak test is recommended as a screening tool for gluten strength in durum wheat breeding programs. Similar support for the GlutoPeak as a fast and reliable tool for predicting bread wheat dough performance and soft wheat technological properties have been reported by others (Amoriello, Turfani, Galli, Mellara, & Carcea, 2016;Marti, Ulrici, Foca, Quaglia, & Pagani, 2015).…”
Section: Comparison Of Glutopeak Test With Other Dough Testssupporting
confidence: 84%
“…It has been suggested SIG could be used as a rapid small-scale test to select for gluten strength in durum wheat breeding (Li et al, 2013). Similar support for the GlutoPeak as a fast and reliable tool for predicting bread wheat dough performance and soft wheat technological properties have been reported by others (Amoriello, Turfani, Galli, Mellara, & Carcea, 2016;Marti, Ulrici, Foca, Quaglia, & Pagani, 2015). The large polymeric fraction is required for strong gluten rheological properties so it is not surprising these strong correlations exist with SIG.…”
Section: Other Small-scale Tests To Predict Gluten Strengthmentioning
confidence: 57%
“…The GlutoPeak (Brabender, Duisburg) device examines gluten aggregation properties, using relatively small flour samples (8.5 g) and short analysis times (<3.0 min) (Fu et al, ; Karaduman et al, ; Lu & Seetharaman, ; Marti et al, ; Melnyk et al ; Wang, Dupuis, & Fu, ), and has been suggested for assessing the gluten strength of soft wheat flour doughs (Amoriello, Turfani, Galli, Mellara, & Carcea, ). Peak maximum time (PMT), maximum torque (BEM), torque before 15 s BEM (AM), torque after 15 s BEM (PM), and aggregation energy (AGG EN) parameters are obtained with the instrument.…”
Section: Resultsmentioning
confidence: 99%
“…Significant relationships were found between glutenin macropolymer content and GlutoPeak PT and PA. Using a stepwise multiple regression, Amoriello et al (2016) suggested the GlutoPeak instrument as a useful tool for assessing protein content, dough strength, and water absorption of soft wheat flour. Similar relationships have been reported for durum semolina between GlutoPeak parameters and gluten strength as measured by mixograph, gluten index, SDS sedimentation, and alveograph parameters (Marti et al 2014a;Sissons 2016).…”
Section: Resultsmentioning
confidence: 99%